Insights into the potential of picoplanktonic marine cyanobacteria strains for cancer therapies – Cytotoxic mechanisms against the RKO colon cancer cell line - Freitas, Sara (2017)
In this work, we analysed the potential of picoplanktonic marine cyanobacteria strains as a source of anticancer compounds by elucidating the cytotoxic mechanisms of an ethyl acetate fraction of Cyanobium sp. (LEGE06113) and the Synechocystis salina (LEGE06155) on the RKO colon adenocarcinoma cell line.